Mexiletine Reverses Oxaliplatin-Induced Neuropathic Pain in Rats - Nobuaki Egashira; Shingo Hirakawa; Takehiro Kawashiri; Takahisa Yano; Hiroaki Ikesue; Ryozo Oishi (Elsevier, 2010)
Oxaliplatin is a platinum-based chemotherapy drug characterized by the development of acute and chronic peripheral neuropathies. Mexiletine, an orally available Na+-channel blocker, has widely been used in patients with chronic painful diabetic neuropathy. In the present study, we examined the effect of mexiletine on oxaliplatin-induced neuropathic pain in rats. Mexiletine (100, but not 10 and 30, mg/kg, p.o.) completely reversed both mechanical allodynia and cold hyperalgesia induced by oxaliplatin (4 mg/kg, i.p., twice a week). Lidocaine (30, but not 3 and 10, mg/kg, i.p.) also significantly relieved both pain behaviors. These results suggest that mexiletine may be effective in relieving the oxaliplatin-induced neuropathic pain clinically. Keywords:: mexiletine, oxaliplatin, neuropathic pain